Totally robotic caudate lobe liver resection: Bridge over troubled water. Issue 6 (29th September 2020) - Cañada Trofo Surjan, Rodrigo; do Prado Silveira, Sergio
Abstract: Background: Minimally invasive hepatectomy has well‐known advantages over the traditional open approach. Inherent limitations of laparoscopy make major hepatectomies and the resection of upper and posterior segments a great technical challenge. The robotic approach overcomes most of these limitations, and this technology is most useful in the resection of the deeply located caudate lobe. Methods: We describe the robotic caudate lobe resection technical aspects, using the first robotic resection of the caudate lobe to treat a biphenotypic hepatocholangiocarcinoma to illustrate the procedure. We also performed a literature review on the current status of the robotic approach to segment (Sg) 1. Results: Technical approach to the robotic caudate lobe resection is described in a patient with uneventful post‐operative recovery. Literature review demonstrated only four previous authors reporting the use of this technique. Conclusion: We present a step‐by‐step approach to the hepatic Sg 1 resection by robotic approach.